Integrating global targets for protected areas and sustainable fisheries - Boris Worm; Ella Clausius; Kirsten Grorud-Colvert; James E. Palardy; Daniel Pauly; Elizabeth P. Pike; Ellen K. Pikitch; Callum M. Roberts; Guinnevere E. Roberts; Robert H. Richmond; Laurenne Schiller; Rick D. Stuart-Smith; et al. (Marine Policy, 2026)

Global Analysis of Shallow Underwater Fish Observation Research: 70 Years of Progress, Persistent Geographic Biases and a Path Forward - Angus John van Wyk; Rick D. Stuart‐Smith; Jordan S. Goetze; Eva Maire; Elodie Heyns‐Veale; Kaylee Smit; Tim J. Langlois; M. Aaron MacNeil; Alejandro Pérez‐Matus; Amanda T. Lombard; Ana Carolina; Christy Semmens; et al. (Fish and Fisheries, 2026)
Marine ecosystems are increasingly threatened by overfishing, pollution, coastal development and climate change, underscoring the need for long‐term, representative information on key fish populations and habitats to inform management and policy. Underwater fish observation (UFObs) techniques, such as Underwater Visual Census (UVC), stereo‐Baited Remote Underwater Video (stereo‐BRUV) and Remotely Operated Vehicles (ROVs), play a key role in sustaining long‐term data collection. Despite technological advancements, gaps persist in understanding research focus, geographic distribution and methodological biases inherent in these methods. We conducted a scientometric analysis of 1443 peer‐reviewed publications (1953–2023), employing natural language processing and network analysis to map the research landscape. We identified 15 knowledge clusters, including marine protected areas, apex predator conservation and reef ecosystems. Our findings reveal increasing use of BRUVS and ROVs in studies of marine protected areas and subsea infrastructure, while UVC remains prevalent in shallow coral reef research. Geographic representation is skewed, with the field dominated by researchers based in Australia and the United States, and underrepresented in Africa and Southeast Asia. This imbalance highlights the need for more inclusive, globally coordinated monitoring and reporting. Our results underscore the urgency of standardising protocols within each observation method and developing interoperable reporting frameworks across techniques to maximise data comparability and foster international collaboration. Addressing these challenges will strengthen the field's capacity to inform global conservation strategies and support sustainable fisheries management.

Climate-driven trans-Tasman population increase of the habitat-modifying, range extending sea urchin Centrostephanus rodgersii - Sterling B. Tebbett; Graham J. Edgar; Celia A. Balemi; John P. Keane; Nick T. Shears; Arie J.P. Spyksma; Rick D. Stuart-Smith; Scott D. Ling (Journal of Environmental Management, 2025)

Biotic Mechanisms Strengthen Functional and Phylogenetic Convergence of Reef Fish Assemblages at Higher Latitudes - Nestor E. Bosch; Rick D. Stuart‐Smith; Katie May Laumann; Graham J. Edgar; Conor Waldock; J. Emmett Duffy; Jonathan S. Lefcheck (Journal of Biogeography, 2025)
Aim How communities of organisms come together has long fascinated scientists, with renewed interest in using functional and evolutionary patterns to infer mechanisms of community assembly. Ecological theory predicts that biotic interactions could lead to either divergence in the event of niche partitioning or convergence through the exclusion of competitively inferior species, but most macroecological studies attribute the latter to environmental influences. Here, we investigated the relative importance of these two opposing mechanisms across broad spatial gradients. We hypothesised stronger signals of: ( i ) convergence at high latitude owing to ecological generalism and ( ii ) divergence at low latitudes owing to specialisation. Major Taxa Studied Reef‐associated bony fishes. Location Global. Time Period 2006–2019. Methods We used a global dataset on marine reef fish assemblages comprising 2476 species at 3325 sites to disentangle the biotic drivers of community assembly across > 100° of latitude. We then applied a framework to remove environmental influences before examining whether any signs of biotic interactions remained in the trait and phylogenetic diversity of local communities relative to the (environmentally constrained) regional species pool, drawing on six functional traits and a phylogeny of bony fishes. Results Local fish assemblages were more functionally and phylogenetically similar to each other than expected based on the regional species pool at higher latitude reefs (i.e., show greater convergence). This pattern was evident after accounting for major sources of local environmental variation, suggesting exclusion of weak competitors. Functional convergence was mainly driven by traits related to resource acquisition, with high‐latitude assemblages converging towards more energetic carnivorous and planktivorous diets. Main Conclusions Our results suggest that biotic interactions drive greater trait and phylogenetic convergence from tropical to temperate zones. Likely mechanisms include increasing generalism and overlap in ecological strategies towards the poles, leading to the exclusion of weak competitors.

Consistent Unimodal Body Length Distributions in Hundreds of Reef Fishes Across Diverse Life Histories - Freddie J. Heather; Shane A. Richards; Nils C. Krueck; Rick D. Stuart‐Smith; Simon J. Brandl; Jordan M. Casey; Graham J. Edgar; Neville Barrett; Valeriano Parravicini; Asta Audzijonyte (Fish and Fisheries, 2025)
Animal body size distributions result from interactions of growth, mortality and recruitment. In ecology and fisheries science, theoretical models of fish body size distributions are widely used but rely on life‐history parameters—growth coefficient (K) and natural mortality rate (M)—that remain unknown for most species and are challenging to estimate. Analysing data from underwater visual surveys and exhaustive sampling, representing 3068 populations across 797 species of shallow‐water, mostly unfished marine fishes, we demonstrate that post‐recruitment body length distributions exhibit a consistent unimodal shape across species and populations. When scaled to the mean body length, these distributions are strikingly similar across all teleost and elasmobranch species, with diverse life histories and maximum body sizes ranging from 1 cm to 3 m. Observed size structure can be approximated by a truncated normal distribution with a coefficient of variation of ~0.34 (SE = 0.002). Such consistent observed body size distributions could be aligned with Beverton–Holt population dynamics theory, if assuming an M/K ratio of ~1.5 and logistic observational selectivity with 50% detectability at ~40% of maximum body length. Alternatively, observed distributions could reflect deviations from theoretical expectations, and reconciling the unimodal distributions with theory may require relaxing some model assumptions, such as continuous recruitment, constant density‐independent growth or constant natural mortality. Overall, the consistency of population‐ and species‐level body length distributions means that unfished size structure could be predicted from a single body size parameter. It also suggests evolutionary convergence of diverse growth and mortality processes towards a narrow range of viable outcomes.

Macroalgae and mobile reef invertebrates face high extinction risk - Olivia J. Johnson; Freddie J. Heather; Jemina Stuart-Smith; Rick D. Stuart-Smith; Camille Mellin; Graham J. Edgar (Biological Conservation, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Contrasting Population Trajectories of Temperate Reef Fishes and Invertebrates Following Seasonal and Multi‐Decadal Temperature Change - Yann Herrera Fuchs; Graham J. Edgar; Neville S. Barrett; Lara Denis‐Roy; Shenae Y. Willis; Hunter Forbes; Rick D. Stuart‐Smith (Global Change Biology, 2025)
Temperature perturbations from climate change affect ecosystems through short‐term pulse events, such as heatwaves, and chronic long‐term shifts. Temperate rocky reef ecosystems have been observed to show substantial ecological change as a result of short‐term temperature fluctuations, but the longer‐term impacts of temperature change remain poorly understood. Here, we investigate temperate reef fishes and mobile invertebrates along Tasmania's east coast, contrasting trends in species richness, abundance, and community structure across seasons within a year to those observed over three decades of warming. Fishes exhibited dynamic seasonal shifts, but interannual changes in richness and abundance balanced out over decades with limited overall net change. In contrast, invertebrate communities changed little seasonally but suffered significant long‐term losses. Our study revealed short‐term ecological changes driven by temperature to be incongruent with long‐term shifts. Species responded in varying ways, depending on life history and ecology. Fishes apparently tracked short temperature pulses, while less mobile invertebrates, such as echinoderms and molluscs, tolerated short‐term fluctuations but exhibited long‐term decline. Multi‐scale studies across a broad range of taxa are needed to clarify thermal responses. The most vulnerable taxa—those facing long‐term thermal stress—may be overlooked through decisions based on short‐term studies, risking major biodiversity loss.

Latitudinal gradients in herbivorous and detritivorous reef fish productivity - Sterling B. Tebbett; Helen F. Yan; Scott Bennett; Graham J. Edgar; Scott D. Ling; Rick D. Stuart-Smith; David R. Bellwood (Reviews in Fish Biology and Fisheries, 2025)

Engineering Performance and Spatial Models Highlight Key Considerations for Supporting Broadscale Replacement of Environmentally Sensitive (ES) Vessel Moorings - Lincoln S. Wong; Andrew Martini; Tim P. Lynch; Carlie Devine; Lauren Hardiman; Felicity R. McEnnulty; Rick D. Stuart-Smith; D. Jeff Ross (Coastal Management, 2025)

Fish and invertebrate communities show greater day–night partitioning on tropical than temperate reefs - Tyson R. Jones; Graham J. Edgar; Rowan Trebilco; Camille Mellin; Rick D. Stuart‐Smith; Lara Denis‐Roy; Olivia J. Johnson; Matthew Rose; Scott D. Ling (Ecology, 2025)
Diel partitioning of animals within ecological communities is widely acknowledged, yet rarely quantified. Investigation of most ecological patterns and processes involves convenient daylight sampling, with little consideration of the contributions of nocturnal taxa, particularly in marine environments. Here we assess diel partitioning of reef faunal assemblages at a continental scale utilizing paired day and night visual census across 54 shallow tropical and temperate reefs around Australia. Day–night differences were most pronounced in the tropics, with fishes and invertebrates displaying distinct and opposing diel occupancy on coral reefs. Tropical reefs in daytime were occupied primarily by fishes not observed at night (64% of all species sighted across day and night, and 71% of all individuals). By night, substantial emergence of invertebrates not otherwise detected during sunlit hours occurred (56% of all species, and 45% of individuals). Nocturnal emergence of tropical invertebrates corresponded with significant declines in the richness and biomass of predatory and herbivorous diurnal fishes. In contrast, relatively small diel changes in fishes active on temperate reefs corresponded to limited nocturnal emergence of temperate invertebrates. This reduced partitioning may, at least in part, be a result of strong top‐down pressures from fishes on invertebrate communities, either by predation or competitive interference. For shallow reefs, the diel cycle triggers distinct emergence and retreat of faunal assemblages and associated trophic patterns and processes, which otherwise go unnoticed during hours of regular scientific monitoring. Improved understanding of reef ecology, and management of reef ecosystems, requires greater consideration of nocturnal interactions. Without explicit sampling of nocturnal patterns and processes, we may be missing up to half of the story when assessing ecological interactions.

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

A framework for optimising opportunistic collaborative syntheses to propel ecological conservation - Ana M.M. Sequeira; Amanda E. Bates; Graeme Hays; David W. Sims; Samantha Andrzejaczek; Asta Audzijonyte; Julia K. Baum; Martin Beal; Barbara Block; Joshua Cinner; Kaitlyn Cowley; Eric Gilman; et al. (Biological Conservation, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Population parameters and conservation implications for one of the world's rarest marine fishes, the red handfish ( Thymichthys politus ) - Tyson J. Bessell; Rick D. Stuart‐Smith; Olivia J. Johnson; Neville S. Barrett; Tim P. Lynch; Andrew J. Trotter; Jemina Stuart‐Smith (Journal of Fish Biology, 2024)
Population estimates are required for effective conservation of many rare marine species, but can be difficult to obtain. The critically endangered red handfish ( Thymichthys politus ) is a coastal anglerfish known only from two fragmented populations in southeast Tasmania, Australia. It is at a high risk of extinction due to low numbers, loss of habitat, and the impacts of climate change. To aid conservation efforts, we provide the first empirical population size estimates of red handfish and investigate other important aspects of the species' life history, such as growth, habitat association, and movement. We surveyed both red handfish local populations via underwater visual census on scuba over 3 years and used photographic mark‐recapture techniques to estimate biological parameters. In 2020, the local adult population size was estimated to be 94 (95% confidence interval [CI] 40–231) adults at one site, and 7 (95% CI 5–10) at the other site, suggesting an estimated global population of 101 adults. Movement of individuals was extremely limited at 48.5 m (± 77.7 S.D. ) per year. We also found evidence of declining fish density, a declining proportion of juveniles, and increasing average fish size during the study. These results provide a serious warning that red handfish are likely sliding toward extinction, and highlight the urgent need to expand efforts for ex situ captive breeding to bolster numbers in the wild and maintain captive insurance populations, and to protect vital habitat to safeguard the species' ongoing survival in the wild.

Rarity mediates species‐specific responses of tropical reef fishes to protection - Loïc Sanchez; Nicolas Loiseau; Graham J. Edgar; Cyril Hautecoeur; Fabien Leprieur; Stéphanie Manel; Matthew McLean; Rick D. Stuart‐Smith; Laure Velez; David Mouillot (Ecology Letters, 2024)
Marine protected areas (MPAs) are the most widely applied tool for marine biodiversity conservation, yet many gaps remain in our understanding of their species‐specific effects, partly because the socio‐environmental context and spatial autocorrelation may blur and bias perceived conservation outcomes. Based on a large data set of nearly 3000 marine fish surveys spanning all tropical regions of the world, we build spatially explicit models for 658 fish species to estimate species‐specific responses to protection while controlling for the environmental, habitat and socio‐economic contexts experienced across their geographic ranges. We show that the species responses are highly variable, with ~40% of fishes not benefitting from protection. When investigating how traits influence species' responses, we find that rare top‐predators and small herbivores benefit the most from MPAs while mid‐trophic level species benefit to a lesser extent, and rare large herbivores experience adverse effects, indicating potential trophic cascades.

Mean reef fish body size decreases towards warmer waters - Amy Rose Coghlan; Julia L. Blanchard; Simon Wotherspoon; Rick D. Stuart‐Smith; Graham J. Edgar; Neville Barrett; Asta Audzijonyte (Ecology Letters, 2024)
Aquatic ectotherms often attain smaller body sizes at higher temperatures. By analysing ~15,000 coastal‐reef fish surveys across a 15°C spatial sea surface temperature (SST) gradient, we found that the mean length of fish in communities decreased by ~5% for each 1°C temperature increase across space, or 50% decrease in mean length from 14 to 29°C mean annual SST. Community mean body size change was driven by differential temperature responses within trophic groups and temperature‐driven change in their relative abundance. Herbivores, invertivores and planktivores became smaller on average in warmer temperatures, but no trend was found in piscivores. Nearly 25% of the temperature‐related community mean size trend was attributable to trophic composition at the warmest sites, but at colder temperatures, this was

Entry fees enhance marine protected area management and outcomes - Chris Brown; Gabby N. Ahmadia; Dominic A. Andradi-Brown; Nur Arafeh-Dalmau; Christina A. Buelow; Max D. Campbell; Graham J. Edgar; Jonas Geldmann; David Gill; Rick D. Stuart-Smith (Biological Conservation, 2023)

Spatial compositional turnover varies with trophic level and body size in marine assemblages of micro‐ and macroorganisms - Amanda K. Pettersen; Melinda A. Coleman; Guillaume Latombe; Sebastian Vadillo Gonzalez; Nathan L. R. Williams; Justin R. Seymour; Alexandra H. Campbell; Torsten Thomas; Renata Ferrari; Rick D. Stuart‐Smith; Graham J. Edgar; Peter D. Steinberg; et al. (Global Ecology and Biogeography, 2022)
Aim Spatial compositional turnover varies considerably among co‐occurring assemblages of organisms, presumably shaped by common processes related to species traits. We investigated patterns of spatial turnover in a diverse set of marine assemblages using zeta diversity, which extends traditional pairwise measures of turnover to capture the roles of both rare and common species in shaping assemblage turnover. We tested the generality of hypothesized patterns related to ecological traits and provide insights into mechanisms of biodiversity change. Location Temperate pelagic and benthic marine assemblages of micro‐ and macroorganisms along south‐eastern Australia (30–36° S latitude). Time period 2008–2021. Major taxa studied Bacteria, phytoplankton, zooplankton, fish, and macrobenthic groups. Methods Six marine datasets spanning bacteria to fishes were collated for measures of “species” occurrence, with a 1° latitude grain. For each assemblage, ecological traits of body size, habitat and trophic level were analysed for the form and rate of decline in zeta diversity and for the species retention rate. Results Species at higher trophic levels showed two to three times the rate of zeta diversity decline compared with lower trophic levels, indicating an increase in turnover from phytoplankton to carnivorous fishes. Body size showed the hypothesized unimodal relationship with rates of turnover for macroorganisms. Patterns of bacterial turnover contrasted with those found for macroorganisms, with the highest levels of turnover in pelagic habitats compared with benthic (kelp‐associated) habitats. The shape of retention rate curves showed the importance of both rare and common species in driving turnover; a finding that would not have been observable using pairwise (beta diversity) measures of turnover. Main conclusions Our results support theoretical predictions for phytoplankton and macroorganisms, showing an increase in turnover rate with trophic level, but these predictions did not hold for bacteria. Such deviations from theory need to be investigated further to identify underlying processes that govern microbial assemblage dynamics.

Tropicalization of temperate reef fish communities facilitated by urchin grazing and diversity of thermal affinities - Jasmin M. Schuster; Rick D. Stuart‐Smith; Graham J. Edgar; Amanda E. Bates (Global Ecology and Biogeography, 2022)
Aim Global declines in structurally complex habitats are reshaping both land‐ and seascapes in directions that affect the responses of biological communities to warming. Here, we test whether widespread loss of kelp habitats through sea urchin overgrazing systematically changes the sensitivity of fish communities to warming. Location Global temperate latitudes. Time period Modern. Major taxa studied Fishes. Methods Community shifts in thermal affinity related to habitat were assessed by simulating and comparing fish communities from 2271 surveys across 15 ecoregions. Results We found that fishes in kelp and urchin barrens differed in realized thermal affinities and range sizes, but only in regions where species pools had high variability in the thermal affinities of species. Barrens on warm temperate reefs host relatively more warm‐affinity fish species than neighbouring kelp beds, highlighting the acceleration of tropicalization processes facilitated by urchin grazing. In contrast, proportionally more cool‐affinity fishes colonize barrens at high temperate latitudes, contributing to community lags with ocean warming in these regions. Main conclusions Our findings implicate urchins as drivers of ecological change, in part by affecting ecological resilience to warming.

Persistent thermally driven shift in the functional trait structure of herbivorous fishes: Evidence of top‐down control on the rebound potential of temperate seaweed forests? - Nestor E. Bosch; Matthew McLean; Salvador Zarco‐Perello; Scott Bennett; Rick D. Stuart‐Smith; Adriana Vergés; Albert Pessarrodona; Fernando Tuya; Tim Langlois; Claude Spencer; Sahira Bell; Benjamin J. Saunders; et al. (Global Change Biology, 2022)
Extreme climatic events can reshape the functional structure of ecological communities, potentially altering ecological interactions and ecosystem functioning. While these shifts have been widely documented, evidence of their persistence and potential flow‐on effects on ecosystem structure following relaxation of extreme events remains limited. Here, we investigate changes in the functional trait structure – encompassing dimensions of resource use, thermal affinity, and body size – of herbivorous fishes in a temperate reef system that experienced an extreme marine heatwave (MHW) and subsequent return to cool conditions. We quantify how changes in the trait structure modified the nature and intensity of herbivory‐related functions (macroalgae, turf, and sediment removal), and explored the potential flow‐on effects on the recovery dynamics of macroalgal foundation species. The trait structure of the herbivorous fish assemblage shifted as a result of the MHW, from dominance of cool‐water browsing species to increased evenness in the distribution of abundance among temperate and tropical guilds supporting novel herbivory roles (i.e. scraping, cropping, and sediment sucking). Despite the abundance of tropical herbivorous fishes and intensity of herbivory‐related functions declined following a period of cooling after the MHW, the underlying trait structure displayed limited recovery. Concomitantly, algal assemblages displayed a lack of recovery of the formerly dominant foundational species, the kelp Ecklonia radiata , transitioning to an alternative state dominated by turf and Sargassum spp. Our study demonstrates a legacy effect of an extreme MHW and exemplified the value of monitoring phenotypic (trait mediated) changes in the nature of core ecosystem processes to predict and adapt to the future configurations of changing reef ecosystems.

Establishing the Foundation for the Global Observing System for Marine Life - Erin V. Satterthwaite; Nicholas J. Bax; Patricia Miloslavich; Lavenia Ratnarajah; Gabrielle Canonico; Daniel Dunn; Samantha E. Simmons; Roxanne J. Carini; Karen Evans; Valerie Allain; Ward Appeltans; Sonia Batten; et al. (Frontiers in Marine Science, 2021)
Maintaining healthy, productive ecosystems in the face of pervasive and accelerating human impacts including climate change requires globally coordinated and sustained observations of marine biodiversity. Global coordination is predicated on an understanding of the scope and capacity of existing monitoring programs, and the extent to which they use standardized, interoperable practices for data management. Global coordination also requires identification of gaps in spatial and ecosystem coverage, and how these gaps correspond to management priorities and information needs. We undertook such an assessment by conducting an audit and gap analysis from global databases and structured surveys of experts. Of 371 survey respondents, 203 active, long-term (>5 years) observing programs systematically sampled marine life. These programs spanned about 7% of the ocean surface area, mostly concentrated in coastal regions of the United States, Canada, Europe, and Australia. Seagrasses, mangroves, hard corals, and macroalgae were sampled in 6% of the entire global coastal zone. Two-thirds of all observing programs offered accessible data, but methods and conditions for access were highly variable. Our assessment indicates that the global observing system is largely uncoordinated which results in a failure to deliver critical information required for informed decision-making such as, status and trends, for the conservation and sustainability of marine ecosystems and provision of ecosystem services. Based on our study, we suggest four key steps that can increase the sustainability, connectivity and spatial coverage of biological Essential Ocean Variables in the global ocean: (1) sustaining existing observing programs and encouraging coordination among these; (2) continuing to strive for data strategies that follow FAIR principles (findable, accessible, interoperable, and reusable); (3) utilizing existing ocean observing platforms and enhancing support to expand observing along coasts of developing countries, in deep ocean basins, and near the poles; and (4) targeting capacity building efforts. Following these suggestions could help create a coordinated marine biodiversity observing system enabling ecological forecasting and better planning for a sustainable use of ocean resources.

Reef communities show predictable undulations in linear abundance size spectra from copepods to sharks - Freddie J. Heather; Rick D. Stuart‐Smith; Julia L. Blanchard; Kate M. Fraser; Graham J. Edgar (Ecology Letters, 2021)
Among the more widely accepted general hypotheses in ecology is that community relationships between abundance and body size follow a log‐linear size spectrum, from the smallest consumers to the largest predators (i.e. ‘bacteria to whales’). Nevertheless, most studies only investigate small subsets of this spectrum, and note that extreme size classes in survey data deviate from linear expectations. In this study, we fit size spectra to field data from 45 rocky and coral reef sites along a 28° latitudinal gradient, comprising individuals from 0.125 mm to 2 m in body size. We found that 96% of the variation in abundance along this ‘extended’ size gradient was described by a single linear function across all sites. However, consistent ‘wobbles’ were also observed, with subtle peaks and troughs in abundance along the spectrum, which varied with sea temperature, as predicted by theory relating to trophic cascades.

High biomass and productivity of epifaunal invertebrates living amongst dead coral - Kate M. Fraser; Rick D. Stuart-Smith; Scott D. Ling; Graham J. Edgar (Marine Biology, 2021)

Direct and indirect effects of heatwaves on a coral reef fishery - Christopher J. Brown; Camille Mellin; Graham J. Edgar; Max D. Campbell; Rick D. Stuart‐Smith (Global Change Biology, 2021)
Marine heatwaves are increasing in frequency and intensity, and indirectly impacting coral reef fisheries through bleaching‐induced degradation of live coral habitats. Marine heatwaves also affect fish metabolism and catchability, but such direct effects of elevated temperatures on reef fisheries are largely unknown. We investigated direct and indirect effects of the devastating 2016 marine heatwave on the largest reef fishery operating along the Great Barrier Reef (GBR). We used a combination of fishery‐independent underwater census data on coral trout biomass ( Plectropomus and Variola spp.) and catch‐per‐unit‐effort (CPUE) data from the commercial fishery to evaluate changes in the fishery resulting from the 2016 heatwave. The heatwave caused widespread, yet locally patchy, declines in coral cover, but we observed little effect of local coral loss on coral trout biomass. Instead, a pattern of decreasing biomass at northern sites and stable or increasing biomass at southern sites suggested a direct response of populations to the heatwave. Analysis of the fishery‐independent data and CPUE found that in‐water coral trout biomass estimates were positively related to CPUE, and that coral trout catch rates increased with warmer temperatures. Temperature effects on catch rates were consistent with the thermal affinities of the multiple species contributing to this fishery. Scaling‐up the effect of temperature on coral trout catch rates across the region suggests that GBR‐wide catches were 18% higher for a given level of effort during the heatwave year relative to catch rates under the mean temperatures in the preceding 6 years. These results highlight a potentially large effect of heatwaves on catch rates of reef fishes, independent of changes in reef habitats, that can add substantial uncertainty to estimates of stock trends inferred from fishery‐dependent (CPUE) data. Overestimation of CPUE could initiate declines in reef fisheries that are currently fully exploited, and threaten sustainable management of reef stocks.

Globally consistent reef size spectra integrating fishes and invertebrates - Freddie J. Heather; Julia L. Blanchard; Graham J. Edgar; Rowan Trebilco; Rick D. Stuart‐Smith (Ecology Letters, 2021)
The frequency distribution of individual body sizes in animal communities (i.e. the size spectrum) provides powerful insights for understanding the energy flux through food webs. However, studies of size spectra in rocky and coral reef communities typically focus only on fishes or invertebrates due to taxonomic and data constraints, and consequently ignore energy pathways involving the full range of macroscopic consumer taxa. We analyse size spectra with co‐located fish and mobile macroinvertebrate data from 3369 reef sites worldwide, specifically focusing on how the addition of invertebrate data alters patterns. The inclusion of invertebrates steepens the size spectrum, more so in temperate regions, resulting in a consistent size spectrum slope across latitudes, and bringing slopes closer to theoretical expectations based on energy flow through the system. These results highlight the importance of understanding contributions of both invertebrates and fishes to reef food webs worldwide.

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

The shape of abundance distributions across temperature gradients in reef fishes - Conor Waldock; Rick D. Stuart‐Smith; Graham J. Edgar; Tomas J. Bird; Amanda E. Bates (Ecology Letters, 2019)
Improving predictions of ecological responses to climate change requires understanding how local abundance relates to temperature gradients, yet many factors influence local abundance in wild populations. We evaluated the shape of thermal‐abundance distributions using 98 422 abundance estimates of 702 reef fish species worldwide. We found that curved ceilings in local abundance related to sea temperatures for most species, where local abundance declined from realised thermal ‘optima’ towards warmer and cooler environments. Although generally supporting the abundant‐centre hypothesis, many species also displayed asymmetrical thermal‐abundance distributions. For many tropical species, abundances did not decline at warm distribution edges due to an unavailability of warmer environments at the equator. Habitat transitions from coral to macroalgal dominance in subtropical zones also influenced abundance distribution shapes. By quantifying the factors constraining species’ abundance, we provide an important empirical basis for improving predictions of community re‐structuring in a warmer world.

Effects of Pollution From Anthropogenic Point Sources on the Recruitment of Sessile Estuarine Reef Biota - Amelia E. Fowles; Graham J. Edgar; Rick D. Stuart-Smith; James B. Kirkpatrick; Nicole Hill; Russell J. Thomson; Elisabeth M. A. Strain (Frontiers in Marine Science, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Fishing‐gear restrictions and biomass gains for coral reef fishes in marine protected areas - Stuart J. Campbell; Graham J. Edgar; Rick D. Stuart‐Smith; German Soler; Amanda E. Bates (Conservation Biology, 2018)
Considerable empirical evidence supports recovery of reef fish populations with fishery closures. In countries where full exclusion of people from fishing may be perceived as inequitable, fishing‐gear restrictions on nonselective and destructive gears may offer socially relevant management alternatives to build recovery of fish biomass. Even so, few researchers have statistically compared the responses of tropical reef fisheries to alternative management strategies. We tested for the effects of fishery closures and fishing gear restrictions on tropical reef fish biomass at the community and family level. We conducted 1,396 underwater surveys at 617 unique sites across a spatial hierarchy within 22 global marine ecoregions that represented 5 realms. We compared total biomass across local fish assemblages and among 20 families of reef fishes inside marine protected areas (MPAs) with different fishing restrictions: no‐take, hook‐and‐line fishing only, several fishing gears allowed, and sites open to all fishing gears. We included a further category representing remote sites, where fishing pressure is low. As expected, full fishery closures, (i.e., no‐take zones) most benefited community‐ and family‐level fish biomass in comparison with restrictions on fishing gears and openly fished sites. Although biomass responses to fishery closures were highly variable across families, some fishery targets (e.g., Carcharhinidae and Lutjanidae) responded positively to multiple restrictions on fishing gears (i.e., where gears other than hook and line were not permitted). Remoteness also positively affected the response of community‐level fish biomass and many fish families. Our findings provide strong support for the role of fishing restrictions in building recovery of fish biomass and indicate important interactions among fishing‐gear types that affect biomass of a diverse set of reef fish families.

Translating local benthic community structure to national biogenic reef habitat types - Anna K. Cresswell; Graham J. Edgar; Rick D. Stuart‐Smith; Russell J. Thomson; Neville S. Barrett; Craig R. Johnson (Global Ecology and Biogeography, 2017)
Aim Marine reef habitats are typically defined subjectively. We provide a continental‐scale assessment of dominant reef habitats through analysis of macroalgae and sessile animal taxa at sites distributed around Australia. Relationships between reef habitats and environmental and anthropogenic factors are assessed, and potential changes in the future distribution and persistence of habitats are considered. Location Shallow rocky and coral reefs around the Australian coast. Methods Cover of 38 sessile biota functional groups was recorded in diver‐based surveys using quadrats at 1,299 sites. Classification analyses based on the functional groups were used to identify an unambiguous set of ‘biogenic habitat types’. Random forest and distance‐based linear modelling were used to investigate correlations between these habitats and environmental and anthropogenic variables. Results Cluster analyses revealed tropical and temperate ‘realms’ in benthic substratum composition, each with finer‐scale habitats: four for the temperate realm (canopy algae, barren, epiphytic algae–understorey and turf) and five for the tropical realm (coral, coral–bacterial mat, turf–coral, calcified algae–coral and foliose algae). Habitats were correlated with different sets of environmental and anthropogenic conditions, with key associations in the temperate realm between mean sea temperature and canopy‐forming algae (negative) and barren habitat (positive). Variation in sea temperature was also an important correlate in the tropical realm. Main conclusions Quantitative delineation of inshore reef habitats at a continental scale identifies many of the same habitat types traditionally recognized through subjective methods. Importantly, many biogenic reef habitats were closely related to environmental parameters and anthropogenic variables that are predicted to change. Consequently, habitats have differing likelihood of persistence. Structurally complex habitats in the temperate realm are at greater risk than more ‘two‐dimensional’ habitats (e.g., canopy‐forming versus turfing algae). In the tropical realm, offshore and coastal habitats differed greatly, highlighting the importance of large‐scale oceanic conditions in shaping biogenic structure.

Quantifying key marine diversity indicators to track the conservation status of shallow Iberian rocky reefs - Becerro Mikel; Bates Amanda; Edgar Graham; Alday Josu; Lazzari Natalí; Martin-Lopez Berta; Palacín Fernández Laura; Sanabria Jose; Sanchez-martinez Nestor; Rodríguez González María; Stuart-Smith Rick (Frontiers in Marine Science, 2016)

Species traits and climate velocity explain geographic range shifts in an ocean‐warming hotspot - Jennifer M. Sunday; Gretta T. Pecl; Stewart Frusher; Alistair J. Hobday; Nicole Hill; Neil J. Holbrook; Graham J. Edgar; Rick Stuart‐Smith; Neville Barrett; Thomas Wernberg; Reg A. Watson; Dan A. Smale; et al. (Ecology Letters, 2015)
Species' ranges are shifting globally in response to climate warming, with substantial variability among taxa, even within regions. Relationships between range dynamics and intrinsic species traits may be particularly apparent in the ocean, where temperature more directly shapes species' distributions. Here, we test for a role of species traits and climate velocity in driving range extensions in the ocean‐warming hotspot of southeast Australia. Climate velocity explained some variation in range shifts, however, including species traits more than doubled the variation explained. Swimming ability, omnivory and latitudinal range size all had positive relationships with range extension rate, supporting hypotheses that increased dispersal capacity and ecological generalism promote extensions. We find independent support for the hypothesis that species with narrow latitudinal ranges are limited by factors other than climate. Our findings suggest that small‐ranging species are in double jeopardy, with limited ability to escape warming and greater intrinsic vulnerability to stochastic disturbances.

Stability in temperate reef communities over a decadal time scale despite concurrent ocean warming - RICK D. STUART‐SMITH; NEVILLE S. BARRETT; DAVID G. STEVENSON; GRAHAM J. EDGAR (Global Change Biology, 2010)
Despite increasing scientific and public concerns on the potential impacts of global ocean warming on marine biodiversity, very few empirical data on community‐level responses to rising water temperatures are available other than for coral reefs. This study describes changes in temperate subtidal reef communities over decadal and regional scales in a location that has undergone considerable warming in recent decades and is forecast to be a ‘hotspot’ for future warming. Plant and animal communities at 136 rocky reef sites around Tasmania (south‐east Australia) were censused between 1992 and 1995, and again in 2006 and 2007. Despite evidence of major ecological changes before the period of study, reef communities appeared to remain relatively stable over the past decade. Multivariate analyses and univariate metrics of biotic communities revealed few changes with time, although some species‐level responses could be interpreted as symptomatic of ocean warming. These included fishes detected in Tasmania only in recent surveys and several species with warmer water affinities that appeared to extend their distributions further south. The most statistically significant changes observed in species abundances, however, were not related to their biogeographical affinities. The majority of species with changing abundance possessed lower to mid‐range abundances rather than being common, raising questions for biodiversity monitoring and management. We suggest that our study encompassed a relatively stable period following more abrupt change, and that community responses to ocean warming may follow nonlinear, step‐like trajectories.

A shift in the habitat use pattern of a lentic galaxiid fish: an acute behavioural response to an introduced predator - Rick D. Stuart-Smith; Robert W. G. White; Leon A. Barmuta (Environmental Biology of Fishes, 2008)